2021
DOI: 10.1186/s40814-021-00931-y
|View full text |Cite
|
Sign up to set email alerts
|

Are some feasibility studies more feasible than others? A review of the outcomes of feasibility studies on the ISRCTN registry

Abstract: Background Feasibility studies are often conducted before committing to a randomised controlled trial (RCT), yet there is little published evidence to inform how useful feasibility studies are, especially in terms of adding or reducing waste in research. This study attempted to examine how many feasibility studies demonstrated that the full trial was feasible and whether some feasibility studies were inherently likely to be feasible or not feasible, based on the topic area and/or research setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The intervention protocol is published in accordance with TIDieR guidelines 34 and reporting of methods and results are transparent and complete in accordance with calls for better reporting of feasibility studies. 58 A novel recruitment strategy was adopted with participants identified via the CCR, meaning invited participants are a nationally representative sample of parents of children treated for cancer. We also successfully adopted an opt-out recruitment strategy and explored reasons for non-participation, 41 which will inform recruitment strategies used in the future pilot RCT.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The intervention protocol is published in accordance with TIDieR guidelines 34 and reporting of methods and results are transparent and complete in accordance with calls for better reporting of feasibility studies. 58 A novel recruitment strategy was adopted with participants identified via the CCR, meaning invited participants are a nationally representative sample of parents of children treated for cancer. We also successfully adopted an opt-out recruitment strategy and explored reasons for non-participation, 41 which will inform recruitment strategies used in the future pilot RCT.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Interestingly, our response rate amongst authors of external pilot trial protocols was lower than authors of external pilot trial results publications. This finding might be explained by publication bias, with non-feasible pilot trial result publications perhaps less likely to be published [ 8 ], and authors more willing to complete the survey where external pilot trials were feasible, had completed and been published. The COVID-19 pandemic likely also impacted and delayed many of the pilot trials included in this study and many might not have proceeded to completion in the timeframe between protocol publication and survey administration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that authors of external pilot trials that do not report progression criteria or report unclear progression criteria, may be optimistic in reporting that a definitive RCT is feasible [ 8 ]. However, our findings indicated only slightly more respondents who did not report clear progression criteria in their external pilot trial publication considered their pilot trial to be feasible or feasible with changes compared to those who did include progression criteria (94%, 32/34 versus 87%, 48/55 respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was updated in 2021 (v2.0, February 2021) to cover all types of preparatory studies and included the expectation that the application would include progression criteria and set out the pathway to RCT [2]. Pre-specifying clear progression criteria facilitate the transparent assessment of pilot trial feasibility and limit the potential for research waste where unfeasible pilot trials progress to unfeasible RCTs [3], and feasible pilot trials do not progress to further research [4].…”
Section: Introductionmentioning
confidence: 99%